The importance of iteration and deployment in technology development: A study of the impact on wave and tidal stream energy research, development and innovation. (December 2015) - MacGillivray, Andrew; Jeffrey, Henry; Wallace, Robin
Abstract: The technological trajectory is the pathway through which an innovative technology develops as it matures. In this paper we model the technological trajectory for a number of energy technologies by analysing technological change (characterised by unit-level capacity up-scaling) and diffusion (characterised by growth in cumulative deployed capacity) using sigmoidal 5 Parameter Logistic (5PL) functions, observed and reported as a function of unit deployment. Application of 5PL functions allows inference of technology development milestones, such as initiation of unit-level up-scaling or industry growth, with respect to the number of unit deployments. This paper compares the technological trajectory followed by mature energy technologies to that being attempted by those in the nascent wave and tidal energy sectors, particularly with regards to unit deployment within a formative phase of development. We identify that the wave and tidal energy sectors are attempting to bypass a formative phase of technological development, which is not in line with technological trajectories experienced by historic energy technologies that have successfully diffused into widespread commercial application, suggesting that demand-pull support mechanisms are premature, and a need for technology push focused policy support mechanisms is vital for stimulating economically sustainable development and deployment of wave and tidal stream energy. Highlights: Technology up-scaling should take place after a formative phase of development. Ocean energy technologies are attempting to bypass a formative phase. Unit up-scaling has taken place prior to successful technology demonstration. The cost of the formative phase may be insurmountable using MW-scale technology. A shift in the research, development and innovation environment is necessary.